Shifting Dynamics of Organizational Culture In Tourism Service Companies In The City Of Surakarta - Wibiyanto*, Agung; Syaifullah, Jahid; Syaifuddin, Makmun; Ikawati, Ratna (Universitas Syiah Kuala, 2024)
The aim of this research is to review the dynamics of organizational culture in tourism service companies in the city of Surakarta and also explain the shift in direction of existing organizational culture. In conducting this research, the Organizational Culture Assessment Instrument (OCAI) was used to assess the condition of the actual company culture and the preferred culture that the company desires to have. It also measures the six dimensions of OCAI and assesses the cultural characteristics of the three samples of tourism service companies in the city of Surakarta. The results of this research show that currently the cultural profile of the three tourism service companies in Solo tends towards a fairly large clan culture pattern and secondly this is followed by a hierarchical culture which also dominates. Meanwhile, the culture that is expected in the next 5 years has shown that the cultural tendencies of hierarchy, adocracy and also the market, considering that in these three patterns of cultural tendencies, considering that the relationship is quite intense and sustainable in accordance with the hierarchical rank levels in each company, will provide greater benefits. intense and certainty in the future of the company regardless of the clan in the three tourism service companies and also some hopes to be increasingly able to compete innovatively by utilizing existing information technology and providing new services to consumers in accordance with what is in the culture adocracy and also culture in the market which is projected for the next 5 years along with a hierarchical culture.